PENENTUAN NILAI PERGERAKAN VERTIKAL PADA TITIK PANTAU DEFORMASI DI KOMPLEK CANDI PRAMBANAN - Widya Hanifazza; Nurrohmat Widjajanti (Universitas Pendidikan Indonesia (UPI), 2022)
Prambanan Temple is one of the largest Hindu temples in Indonesia that has been declared one of the world heritage sites by UNESCO in 1991. The soil structure underneath the temples consists of Young Mount Merapi and sand sediments characterized as a light structure. It can shift quickly, making Prambanan Temple susceptible to vertical movements. Geodetic measurement was held periodically using Total Station, but there has not been any comprehensive analysis for the vertical movements. The study generated computation for the vertical movements of the monitoring point located on the body of the Prambanan Temple. Then an analysis of the vertical movement was generated. This computation uses observations data of the vertical angles and horizontal distance for the first- period (2019) and the second-period measurement (2020) from the deformation monitoring points spread across six temples in the yard of Prambanan Temple. The height value (Z) and standard deviation are computed using a general least square adjustment method. The vertical deformation is analyzed by a statistical test which consists of a significance test for different parameters and a single point displacement test using a confidence level of 95%. Furthermore, analysis of the vertical movement velocity is carried out at each monitoring point. The result is the Z value for the second-period measurement along with its precision, the value of vertical movement, and the velocity of vertical movement at each monitoring point. The Z value obtained in the second-period measurement has a standard deviation value of less than 4 mm, ranging from 0,322 to 3,096 mm.